Sarcopenia and Systemic Inflammation Response Index Predict Response to Systemic Therapy for Hepatocellular Carcinoma and Are Associated With Immune Cells - Zhao, Man; Duan, Xiaoling; Han, Xin; Wang, Jinfeng; Han, Guangjie; Mi, Lili; Shi, Jianfei; Li, Ning; Yin, Xiaolei; Hou, Jiaojiao; Yin, Fei (Frontiers in Oncology, 2022)
Background Systemic therapies, including immune checkpoint inhibitors (ICIs) and tyrosine kinase inhibitors (TKIs), have challenged the use of conventional therapies for hepatocellular carcinoma (HCC). It is crucial to determine which patients could benefit most from combination therapy. This study aims to examine the associations of sarcopenia and systemic inflammation response index (SIRI) with the treatment responses and efficacies in patients with HCC treated with ICIs and tyrosine kinase inhibitors TKIs, as well as investigate the correlation between sarcopenia and inflammatory or immune states. Methods We reviewed 160 patients with HCC treated with TKIs and ICIs. The patients’ psoas muscle size was measured on axial computed tomography scans and normalized for the patients’ height squared. This value was referred to as the psoas muscle index (PMI). Sarcopenia was determined from PMI and their relationships with patients’ clinicopathological characteristics, inflammation indexes, peripheral blood T-cell subsets and survival were evaluated. Results Sarcopenia and systemic inflammation response index (SIRI) were independent predictors for overall survival and progression-free survival. Patients with high PMI and low SIRI demonstrated significantly better median overall survival and progression-free survival (36.0 months and 9.6 months, respectively) than those with either low PMI or high SIRI (20.8 months and 6.0 months, respectively) and those with both high SIRI and low PMI (18.6 months and 3.0 months, respectively). Portal vein tumor thrombus (P=0.003), eastern cooperative oncology group performance status score of 1 (P=0.048), high alkaline phosphatase (P=0.037), high neutrophil-to-lymphocyte ratio (NLR) (P=0.012), low lymphocyte-to-monocyte ratio (LMR) (P=0.031), high platelet-to-lymphocyte ratio (PLR) (P=0.022) and high SIRI (P=0.012) were closely associated with an increased incidence of sarcopenia. PMI was negatively correlated with SIRI (r = -0.175, P=0.003), NLR (r = -0.169, P=0.036), and PLR (r = -0.328, P=0.000) and was significantly positively correlated with LMR (r = 0.232, P=0.004). The CD3+ and CD4+ T-cell counts of the high PMI group were significantly higher than those of the low PMI group. Conclusion Sarcopenia and high SIRI were associated with reduced survival in patients with HCC treated with ICIs and TKIs. Sarcopenia could affect inflammatory states and the immune microenvironment.